1992
DOI: 10.1111/j.1467-9507.1992.tb00132.x
|View full text |Cite
|
Sign up to set email alerts
|

The conversational skills of school‐aged children

Abstract: Differences associated with age and with language background were assessed in performance on a task that taps conversational skill, a 'TV talk show' interview task administered to 98 second through fifth graders, including many nonnative speakers of English. Surprisingly, holistic ratings ofthe children's skills as conversationalists were not related at all to gender, and only moderately to age or status as a native speaker of English. A set of 29 specific interactive and language behaviors were analyzed, to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…The relations between self-repetition and participation may reflect characteristics of peer interaction. Compared to adult-child interaction, which has been observed to be question-driven to a large extent (Beals, 1991;Callanan & Oakes, 1992;Schley & Snow, 1992), questions were infrequent in the peer interaction observed (see also Aukrust, 2004). Children became participants by throwing themselves into the interaction, not by responding to conversational invitations.…”
Section: Discussionmentioning
confidence: 90%
“…The relations between self-repetition and participation may reflect characteristics of peer interaction. Compared to adult-child interaction, which has been observed to be question-driven to a large extent (Beals, 1991;Callanan & Oakes, 1992;Schley & Snow, 1992), questions were infrequent in the peer interaction observed (see also Aukrust, 2004). Children became participants by throwing themselves into the interaction, not by responding to conversational invitations.…”
Section: Discussionmentioning
confidence: 90%
“…What initially sounds "correct" may mask a misconception. Previous research has also described how children need help from adults to provide detailed information during conversations (Sehley and Snow 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Next, the researcher and the two independent researchers coded the role play data for several verbal features of pragmatic competence that previous research had shown to be good indicators of pragmatic competence. These features include the number of words, context-specific vocabulary words, and utterances (Bachman, Vanniarajan & Lynch, 1988;Brown, 1973;Larsen-Freeman & Stormy, 1977;Robinson, 1989;Rollins, Snow, & Willet, 1996) and the skills used to manage interaction and meaning management, including formulaic expressions, initiations, elaborations, conversation conclusions, and self-and othercorrections (Ninio & Snow, 1996;Sacks, Schegloff, & Jefferson, 1974;Schley & Snow 1992). As used here, formulaic expressions were defined as unanalyzed chunks or prepatterned phrases used recurrently and extensively in an effort to initiate or maintain conversation.…”
Section: Data Analysis Proceduresmentioning
confidence: 99%